Multi-Project Report: Physical Activity and Nutrition Promotion in Riley County, Kansas - Hunt, Shelby Hunt (My University, 2021)
Project 1: College of Veterinary Medicine Counseling Services Veterinary medical school requires immense levels of dedication to academic performance and clinical expertise. Students encounter numerous stressors including perceived lack of time for recreational and social activities, chronic sleep deprivation, constant evaluation, academic concerns, and poorly perceived physical health. As such, veterinary students are confronted with a variety of mental health concerns including increased risk of depression, anxiety, and substance abuse. As suicide among practicing veterinary professionals continues to rise, Counseling Services at Kansas State University’s (K-State) College of Veterinary Medicine (CVM) has identified a need to address mental health within the profession. With the assistance of numerous stakeholders, including myself, CVM Counseling Services developed a health promotion program coined “Well Vets Well Pets.” The Well Vets Well Pets incentive program intended to use physical activity to promote improvements in mental health, alongside mental health awareness and mindfulness practices. The program faced adversity in light of the COVID-19 pandemic, but nonetheless was launched virtually on CVM social media platforms in the Fall of 2020. Program planning and implementation will be discussed in regard to preliminary data interpretation. Project 2: K-State Research and Extension of Riley County Individuals experiencing food insecurity are at greater risk for negative health outcomes compared to individuals who are not experiencing food insecurity, due to changes in food intake and decreases in dietary variety. Adults experiencing food insecurity are more likely to develop chronic diseases such as heart disease, cancer, diabetes, and obesity as well as engage in negative health behaviors such as smoking. Due to COVID-19, Feeding America projects that the 2020 food insecurity rate in Riley County will increase from 12.9% to 15.8%. There are many organizations in Riley County devoted to decreasing food insecurity. However, K-State Research and Extension found that community members in need of food are often lacking the necessary equipment to safely prepare it. Therefore, K-State Research and Extension partnered with the Food and Farm Council of Riley County and Manhattan, Kansas to develop the Kitchen Restore program. Kitchen Restore aims to provide low-income community members with kitchen essentials as well as the skillset to use them. While I participated in a number of projects for K-State Research and Extension, the majority of my efforts were focused on Kitchen Restore. The program’s nutrition education and promotion efforts are discussed herein.
Keywords: veterinary medical school; mental health; physical activity; nutrition; food insecurity